Research on Network Routing Control Algorithm Based on OpenFlow and IGP. Issue 1 (1st March 2022) - Tian, Xuejun; Wen, Lizi; Yang, Xingyan; Chen, Liangzhe; Min, Gang; Shu, Zhong
Abstract: Given the coexistence of heterogeneous hybrid networks such as IP network, 4G network and Software Defined Network (SDN) in the application of digital news media system, this paper designs a routing control algorithm based on SDN network architecture, which can realize the compatibility of internal gateway protocol and OpenFlow communication strategies. Through the analysis of OpenFlow communication protocol in SDN network architecture, the relationship between Interior Gateway Protocol (IGP) and OpenFlow routing rules is found out. Based on the existing hardware structure of the OpenFlow router, the configuration parameters of a port table, port address table and routing table are improved, and the adjacent routing relation table and information transmission port are used to realize the connection between routers are designed. The attention of users is considered It can reduce the burden of system operation and is compatible with the forwarding control of route forwarding and routing filtering. The adjacent routing relation table is designed to control the process of data collection, storage and forwarding, and the input and output ports between adjacent routers are defined. The open router designed in this paper integrates Simple Network Management Protocol (SNMP) agent and SDN agent mechanism organically to achieve the goal of SDN network management; the routing control module focuses on the management of key data flow, realizes the control of routing state and data flow at the same time, and provides the visualization function of routing state and routing state data flow. By constructing the experimental platform of routing transmission and control functions based on routing control and interior gateway protocol, the effect of routing state control of the two methods is compared and analysed from three aspects of packet transmission state, packet processing state and packet receiving delay in routing control process. The experimental results verify the correctness of the design results.